1972
DOI: 10.1042/bj1260515
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the protein–polysaccharides of pig articular cartilage during prenatal life, development and old age

Abstract: Analysis of the knee-joint cartilage of pigs at five ages (namely foetuses from the second half of pregnancy and animals 10 weeks, 25 weeks, 3 years and 5 years old) showed that the composition approached that of adult cartilage by 25 weeks of age, the most marked differences being between foetal and 10 week-old cartilage. Protein-polysaccharides were extracted sequentially, first by brief low-speed homogenization with iso-osmotic sodium acetate, then by two extractions with 2m-CaCl(2) for 24h with gentle agit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

1972
1972
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(19 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…In previous studies we found similar differences in other species: baboons, pigs, and rats [13; Stanescu el a!., unpublished]. By using different methods, Brandt and M uir [4] and Simunek and M uir [22] found differences in the proteoglycans of the pig articular cartilage during prenatal life, development and old age. Further studies are necessary to establish the period in which the pattern of fetal proteoglycans of the human growth cartilage is changed into that found in older children.…”
Section: Discussionmentioning
confidence: 49%
“…In previous studies we found similar differences in other species: baboons, pigs, and rats [13; Stanescu el a!., unpublished]. By using different methods, Brandt and M uir [4] and Simunek and M uir [22] found differences in the proteoglycans of the pig articular cartilage during prenatal life, development and old age. Further studies are necessary to establish the period in which the pattern of fetal proteoglycans of the human growth cartilage is changed into that found in older children.…”
Section: Discussionmentioning
confidence: 49%
“…A varied population of protein-polysaccharides has also been demonstrated in porcine cartilage of different anatomical origins (10,11). Simuinek and Muir (12) have recently shown that larger molecular weight protein-polysaccharides of pig articular cartilage predominate during prenatal life, as compared to early postnatal development and old age. Our results suggest that chick embryonic cartilage produces a larger molecule than that of adult cartilage.…”
Section: Methodsmentioning
confidence: 99%
“…Such changes in proteoglycan structure are not unique to the human, but have also been shown in a variety of animals (10)(11)(12)(13)(14)(15)(16). Again, the changes in glycosylation appear to be predominant between birth and the end of growth (17).…”
mentioning
confidence: 92%